Revision or Revolution? A Note on Behavioral vs. Neoclassical Economics - Ronald Schettkat (University of Wuppertal, Schumpeter School of Business and Economics, 2018)
Behavioral economics, the analysis of economic decisions, has made enormous progress over the last decades and became accepted as a major field in economics. How is behavioral economics to be compared to the neoclassical model? As a revision of the neoclassical model enhancing the set of variables for motivation such as fairness in the utility function which is then to be maximized? Or is behavioral economics a revolution, a departure from the neoclassical axioms, a new model? This paper argues that many of the findings in behavioral economics are incompatible with the neoclassical model and have paved the way for a revolution in economics.
urn:nbn:de:hbz:468-20180606-104034-4
Keywords: 330; Behavioral Economic; Neoclassical Economics; Economic Theory; Economic Methodology